Risk factors for neck and upper extremity disorders among computer users and the effect of interventions: an overview of systematic reviews. (19th October 2011) - Andersen, Johan Hviid; Fallentin, Nils; Thomsen, Jane Frølund; Mikkelsen, Sigurd
Abstract : Objectives: To summarise systematic reviews that 1) assessed the evidence for causal relationships between computer work and the occurrence of carpal tunnel syndrome (CTS) or neck and upper extremity musculoskeletal disorders (UEMSDs), or 2) reported on intervention studies among computer users /or office workers. Methods: Four databases were searched for reviews published between 1999 and 2010. Primary author extracted all data using a purpose-built form, while two of the authors evaluated the quality of the reviews using recommended standard criteria AMSTAR; disagreements were resolved by discussion. The quality of evidence syntheses in the included reviews was assessed qualitatively for each outcome and for the interventions. Results: Altogether, 1349 review titles were identified, and 17 reviews were finally included as being of sufficient quality. Three reviews on risk factors for carpal tunnel syndrome were rated moderate to high quality, 8 reviews on risk factors for UEMSDs ranged from low to moderate/high quality, and 6 reviews on intervention studies were of moderate to high quality. The quality of the evidence for computer use as a risk factor for CTS was insufficient, while the evidence for computer use and UEMSDs was moderate regarding pain complaints and limited for specific musculoskeletal disorders. From the reviews on intervention studies no strong evidence based recommendations could be given. Conclusions: Computer use is associated with pain complaints, but it is still not very clear if this association is causal. The evidence for specific disorders or diseases is limited. No effective interventions have yet been documented.